Political Constellation in Shaping Voter Preferences: Case Study of the 2024 Makassar Mayoral Election - Hawing, Hardianto; Alim, Irwan; Hartaman, Nursaleh (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
The 2024 Makassar Mayoral Election is part of Indonesia's nationwide simultaneous local elections (Pilkada), which garners significant attention due to the city’s unique and dynamic political context. This study aims to analyze the political preferences of Makassar residents during the 2024 election using a qualitative case study approach. The research data were obtained from official government institutions, such as the General Elections Commission and the Makassar City Government, along with various online media platforms. The findings reveal that voter preferences are shaped by multiple interrelated factors, political party coalitions, the public image of candidates, key campaign issues, and the persistence of transactional politics. A particularly notable finding is the relatively low voter turnout, recorded at only 57.7%, which is below both the national target and the participation rate of previous elections.This study confirms that political preferences in Makassar are driven by the interplay of candidate personality traits and the local socio-political environment. It highlights the continuing influence of patron-client relationships and money politics, alongside emerging patterns of issue-based and image-based voting. These insights underscore the importance of strengthening political education and enhancing electoral integrity to improve democratic quality at the local level in future elections